PENGARUH LATIHAN MANUVER POPLITEAL ANGLE TERHADAP PERUBAHAN SUHU PADA BAYI BARU LAHIR - ., Suryanti (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2015)
ABSTRACT: Hipotermi in the newborn can lead to problems that often arise after the baby is born that pervalensinya numbers are quite high. Hipotermi can cause complications such as brain damage, acidosis, hypoglycemia, lowering systemic blood pressure and death. One way to increase the body temperature of an infant with popliteal angle maneuver exercise, i.e. the mechanism movement extension that Flex the knee, stretch your hip joint, which will affect the blood vessels so that will be pumping blood throughout the body to increase the metabolism of the body so the body temperature increases. Sources of energy in the newborn in the form of glucose is derived from protein and fats Brown, to produce energy required ATP. It is this mechanism can cause changes in body temperature of an infant. The purpose of this research is to know the influence of popliteal angle maneuver exercises against temperature changes in the newborn. This research uses a quantitative design, with associative methods. The subjects in this study as many as 32 newborn ... The data obtained through the popliteal monuver angle drills Cheklist. The data analysis technique used to analyze problems with the formulation of the hypothesis of this research using Spearman Rank Correlation. The results of the data analysis based on hypothesis testing found the probability figures the figures below, 0.000 0.05 Ha Ho was rejected and then accepted or there is actual significant effects. The value of the correlation coefficient obtained figures + 0.762 76.2% which is about the powerful numbers between before and after the action. Summary of the research is there is the influence of the politeal angle maneuver exercises against temperature changes in the newborn. Â Key words: temperature changes in the newborn, exercises Maneuvers Popliteal Angle